Magisterium of the Church in the Face of New Interpretations of the Dogma of Original Sin - Łukaszuk, Tadeusz (Studia Theologica Varsaviensia, 2020)
Anyone who closely observes the relationship between the Magisterium and theology in recent years with regard to original sin feels a twofold statement being imposed: first, theologians have not ceased to preach new interpretations of the dogma of original sin even if they do not agree with everything in the postulates contained in the statements of the Magisterium of the Creed of Paul VI inclusiveB&; second, the Magisterium of the Church does not speak out on this matterB(. ese two parallel facts, constituting a certain problem, at the same time form the basis for solving it.